2014
DOI: 10.1371/journal.pone.0113224
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Effects in the Folding of the SH3 Domain of the c-Src Tyrosine Kinase: pH-Dependence in 3D-Domain Swapping and Amyloid Formation

Abstract: The SH3 domain of the c-Src tyrosine kinase (c-Src-SH3) aggregates to form intertwined dimers and amyloid fibrils at mild acid pHs. In this work, we show that a single mutation of residue Gln128 of this SH3 domain has a significant effect on: (i) its thermal stability; and (ii) its propensity to form amyloid fibrils. The Gln128Glu mutant forms amyloid fibrils at neutral pH but not at mild acid pH, while Gln128Lys and Gln128Arg mutants do not form these aggregates under any of the conditions assayed. We have al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 77 publications
2
27
0
Order By: Relevance
“…Thus, the Fyn SH3domain crystal structure contains two molecules in the asymmetric unit with different conformations, the same as the crystal structure of the c-Src SH3 domain. Each molecule has a different conformation: chain B contains the same water molecules w1 and w2 as found in the Fyn SH3-VSL12 complex, while chain A does not (Bacarizo et al, 2014). Additionally, Leu101 (Leu100 in c-Src SH3) shows different conformers in each chain and we have proposed a relevant role of this residue in the conformational changes that take place to accommodate the binding of PRMs in the two available orientations (Bacarizo et al, 2015).…”
Section: Comparison Of the Hydration Spots Present In The Fyn Sh3 Commentioning
confidence: 78%
“…Thus, the Fyn SH3domain crystal structure contains two molecules in the asymmetric unit with different conformations, the same as the crystal structure of the c-Src SH3 domain. Each molecule has a different conformation: chain B contains the same water molecules w1 and w2 as found in the Fyn SH3-VSL12 complex, while chain A does not (Bacarizo et al, 2014). Additionally, Leu101 (Leu100 in c-Src SH3) shows different conformers in each chain and we have proposed a relevant role of this residue in the conformational changes that take place to accommodate the binding of PRMs in the two available orientations (Bacarizo et al, 2015).…”
Section: Comparison Of the Hydration Spots Present In The Fyn Sh3 Commentioning
confidence: 78%
“…To elucidate the mechanism we computed the underlying FES of domain swapping in a single domain globular protein, cSrc-SH3, which is found to form intertwined domain swapped dimers. 46,51 We used coarse-grained SOP-SC model of the Q128E mutant of the dimeric crystal structure 51 (PDB ID: 3FJ5) as a reference system ( Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…The above results showed that promiscuous binding of peptide molecule can be effectively ameliorated by rational design. Based on various public crystallographic data, [33][34][35][36][37][38] the SH3 domain has been thoroughly researched and broadly recognized as one of the best available systems for the examination of ligand-protein interactions. For example, Larson et al constructed a diverse alignment of SH3 domain sequences.…”
Section: Implication Of the Current Resultsmentioning
confidence: 99%